Influences of nationality and national identification on perceived dangerousness of COVID-19 variants and perceived effectiveness of COVID-19 vaccines: A study of UK and Portuguese samples - Breakwell, G. M.; Camilo, C.; Jaspal, R.; Lima, M. L. (Journal of Social and Political Psychology, 2022)
During the COVID-19 pandemic, both variants of the virus that causes the disease and vaccines developed to combat it have been identified with nationalities. Both social identity theory and identity process theory would predict that this would initiate intergroup differentiation processes aimed at optimizing ingroup value and personal identity enhancement. Our study examined whether people’s nationality and level of national identification influence their perception of dangerousness of variants and effectiveness of vaccines. We compared data collected by online survey in March 2021 from the UK (which was associated with both a variant and a vaccine) and Portugal (which was associated with neither). The Portuguese rated variants overall as more dangerous than did the UK sample. The Chinese variant was rated by both samples as the least dangerous and the UK sample rated the British variant as less dangerous than did the Portuguese. Higher national identification in the UK sample was associated with differentiating more between the British variant and the South African variant and differentiating it less from the Chinese variant. The UK sample rated the effectiveness of the British vaccine higher than did the Portuguese. They also evaluated it as more effective than the American, Chinese and Indian vaccines. In both samples, higher national identification was associated with lower ratings of effectiveness for vaccines originating in China or India. Our study suggests that identity processes associated with national identification do influence perceptions of vaccines and variants. This has significant practice and policy implications. Social representations of variants and vaccines in nationalistic terms can have complex and unexpected consequences.